AUTOMATION OF HR ADMINISTRATIVE TASKS USING AI CHATBOTS: AN EMPIRICAL STUDY ON EFFICIENCY AND USER EXPERIENCE (Contemporary Journal of Social Science Review, 2025)
The adoption of Artificial Intelligence (AI) chatbots in Human Resources (HR) represents a revolutionary shift toward operational efficiency. This paper explores how far AI chatbots can be used to automate standard HR administrative procedures, such as employee onboarding, leave requests, and payroll inquiries, without compromising the quality of employee interactions. Using a mixed-methods approach, quantitative data on the time and accuracy of task completion were collected before and after the implementation of chatbots in three mid-sized organizations. The qualitative data were collected through structured interviews with HR personnel and employees to understand usability and satisfaction. Findings show that task-handling time (mean reduction: 58) and procedural errors were significantly reduced. Nevertheless, qualitative data indicated that complex or emotionally sensitive problems could not be processed effectively, underscoring the importance of a hybrid human-AI model. The research finds that AI chatbots are powerful administrative efficiency tools, but should be used as supplementary aids and not complete replacements of human HR functions.